Optimizing Scientific Literacy Through Differentiated Instruction Based on Problem Based Learning (PBL) in Grade VII Students at SMP Negeri 7 Tidore Kepulauan - Lestari, Fitri Ayu; Ismail, Agus R. Hi.; Faradina, Faradina; Ihsan, Ikhlashul (Peneliti.net, 2025)
This study aims to improve students’ science literacy at SMP Negeri 7 Tidore Kepulauan through the implementation of differentiated learning based on Problem Based Learning (PBL). The research design used is a quasi-experiment with a pretest-posttest control group. The research sample consisted of two groups: the experimental group, which implemented differentiated learning based on PBL, and the control group, which followed conventional instruction. Data were collected through science literacy tests, classroom observations, and interviews. The analysis results showed a significant improvement in science literacy among students in the experimental group compared to the control group. The average post-test score of the experimental group reached 82.30, while the control group scored 67.46. The independent sample t-test showed a significant difference between the two groups (p < 0.05). These findings indicate that the differentiated PBL approach is effective in optimizing students’ science literacy skills. The implications of this research support the implementation of learning strategies that are responsive to students’ needs within the context of the Merdeka Curriculum.